2014
DOI: 10.1080/19425120.2013.866999
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Fish Movement Responses to and Potential Salinity Stress from Large‐Scale River Diversions

Abstract: River diversions are a major but controversial management approach to restoring coastal wetlands and mitigating offshore oil spills in the northern Gulf of Mexico. One of the controversies concerns the potential displacement of and salinity stress on commercially and recreationally important fish species in response to the widespread and prolonged freshening of habitat. We developed a coupled hydrodynamics–fish movement model and applied it to the Caernarvon diversion located in the Breton Sound estuary, Louis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 59 publications
(55 reference statements)
1
21
0
Order By: Relevance
“…Freshwater diversions are used to divert water from the Mississippi River to help enhance wetland vegetation and re-nourish marsh ecosystems (DeLaune et al 2003). Normally, large quantities of freshwater are allowed to flow through the structures during the cooler winter and early spring months of each year because of potential impacts to oysters and other fisheries that would result from exposure to lower-salinity waters during the warmer summer months (Turner 2006, La Peyre et al 2013, Rose et al 2014. In 2010, these diversions remained opened for significantly longer and at a higher flow rate than in previous years.…”
mentioning
confidence: 99%
“…Freshwater diversions are used to divert water from the Mississippi River to help enhance wetland vegetation and re-nourish marsh ecosystems (DeLaune et al 2003). Normally, large quantities of freshwater are allowed to flow through the structures during the cooler winter and early spring months of each year because of potential impacts to oysters and other fisheries that would result from exposure to lower-salinity waters during the warmer summer months (Turner 2006, La Peyre et al 2013, Rose et al 2014. In 2010, these diversions remained opened for significantly longer and at a higher flow rate than in previous years.…”
mentioning
confidence: 99%
“…Rose et al. ). Validation of the habitat suitability model using Pensacola Bay data to predict Choctawhatchee Bay habitat suggested that inter‐estuarine variability, even within local geographic regions, bears further consideration before habitat models are used to predict species distribution in a region where occupancy data was not collected empirically.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these 187 sites were also chosen for eval uation under the NRDA-sponsored marsh edge and sandy shoreline study and the coastal vegetation study (www.gulfspillrestoration.noaa.gov/oilspill/ gulf-spill-data/ (Martínez et al 2012, Rose et al 2014, releasing 212 000 l s −1 (Davis Pond) and 226 000 l s −1 (Caernarvon) of Mississippi River water directly into those estuaries. Normally these structures are opened only during the cooler winter and early spring months of each year because of potential impacts to oysters and other fisheries from low-salinity water exposure during the warm late-spring and summer months (Turner 2006, Rose et al 2014). The additional sampling locations were probabilistically selected using the generalized random tessellation stratified sampling procedure (Stevens & Olsen 1999.…”
Section: Site Selectionmentioning
confidence: 99%